A comparative analysis of risk stratification tools in SSc-associated pulmonary arterial hypertension: a EUSTAR analysis. - Bjørkekjær, Hilde Jenssen; Bruni, Cosimo; Broch, Kaspar; Brunborg, Cathrine; Carreira, Patricia E.; Airò, Paolo; Simeón-Aznar, Carmen Pilar; Truchetet, Marie Elise; Giollo, Alessandro; Balbir-Gurman, Alexandra; Martin, Mickael; Denton, Christopher P.; et al. (Rheumatology, 2025)
OBJECTIVES: The 2022 European Society of Cardiology and European Respiratory Society (ESC/ERS) guidelines for pulmonary arterial hypertension (PAH) recommend risk stratification to optimize management. However, the performance of generic PAH risk stratification tools in patients with SSc-associated PAH remains unclear. Our objective was to identify the most accurate approach for risk stratification at SSc-PAH diagnosis. METHODS: In this multicentre, international cohort study from the European Scleroderma Trials and Research (EUSTAR) group database, we screened 11 risk stratification tools upon SSc-PAH diagnosis. We compared the performance of the three top-ranked tools to predict mortality with the ESC/ERS three-strata model, the currently recommended tool for baseline risk assessment. We also assessed the impact of incorporating SSc-specific characteristics into the tools. Kaplan-Meier analyses and Cox regression with area under the ROC curve (AUC) were conducted. RESULTS: The ESC/ERS three-strata model had a lower ability to predict mortality than the ESC/ERS four-strata model, 'SPAHR updated' and 'REVEAL Lite 2'. The ESC/ERS four-strata model divided 'intermediate-risk' patients into two groups with significantly different long-term survival rates and is the easiest applicable tool. Incorporating SSc-specific characteristics did not significantly improve the predictive ability of any model, but a low diffusing capacity of the lung for carbon monoxide (DLCO) was an independent predictor of mortality. CONCLUSION: Considering its ability to predict mortality, risk segregation capabilities and clinical applicability, this study provides a rationale for using the simplified ESC/ERS four-strata model at SSc-PAH diagnosis as an alternative to the comprehensive ESC/ERS three-strata model. We propose considering DLCO as an individual prognostic marker in SSc-PAH.
EVALuna2:615639